Intervensi New Media dan Impersonalisasi Otoritas Keagamaan di Indonesia - Jinan, Mutohharun (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2013)
The article discusses the impact of new media on the shift of religious authority in Indonesia. It argues that the development of new media (internet) has shifted the traditional religious authority to more impersonal media such as books, websites, blogs, and the like. Furthermore, progressiveness and openness of the new Media also have supported the acceleration on the so called “Ulama rejuve–nation”. This is due to the fact that, due to such shift (the religious power shifting), a person does not necessarily graduate from pesantren to be Muslim clerics or Ulama. In addition, the shift of religious authority also has contribu–ted to the loosening filter for the emergence of a wide variety religious intereptations that, to some extent, go uncontrolled without limitation.Keywords: new media, religious authority, impersonal media———————————————————————-Artikel ini mendiskusikan dampak new media pada pergeseran otoritas keagamaan di Indonesia, dan berpendapat bahwa seiring perkembangan teknologi in–formasi, internet telah memudarkan otoritas keagamaan tradisional dan bergeser pada pada media impersonal, se–perti buku, website, blog, dan sejenisnya. Progresifitas dan keterbukaan new media juga mendorong percepatan pro–ses ”peremajaan ulama” yang tidak mensyaratkan bahwa ulama harus lulusan dari pesantren. Selain itu, intervensi new media memungkinkan percepatan merebaknya pema–haman ”liar” yang sangat berbeda dari arus mainstream. Arus pertumbuhan new media ini tentunya semakin memencarnya fatwa-fatwa keagamaan tanpa batas-batas yang jelas.Kata Kunci: new media, otoritas keagamaan, media impersonal